2024
DOI: 10.1101/2024.01.30.577120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical confinement governs phenotypic plasticity in melanoma

Miranda V. Hunter,
Emily Montal,
Yilun Ma
et al.

Abstract: Phenotype switching is a form of cellular plasticity in which cancer cells reversibly move between two opposite extremes - proliferative versus invasive states. While it has long been hypothesised that such switching is triggered by external cues, the identity of these cues has remained elusive. Here, we demonstrate that mechanical confinement mediates phenotype switching through chromatin remodelling. Using a zebrafish model of melanoma coupled with human samples, we profiled tumor cells at the interface betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 105 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…While jamming-unjamming transitions have become a well-established framework to explain cancer invasion, the underlying biological mechanisms are poorly understood. Recent studies have revealed possible mechanisms that impact plasticity pathways such as the ERK1/2 pathway, which triggers cell motility and results in collective invasive strands 16 , and a mechanosensitive pathway, in which cellular confinement directly causes deformations of the cell nuclei accompanied by chromatin remodelling 69 . Here we showed evidence that EMT is also a mechanism involved in 3D unjamming transitions by regulating cell-matrix interplay.…”
Section: Discussionmentioning
confidence: 99%
“…While jamming-unjamming transitions have become a well-established framework to explain cancer invasion, the underlying biological mechanisms are poorly understood. Recent studies have revealed possible mechanisms that impact plasticity pathways such as the ERK1/2 pathway, which triggers cell motility and results in collective invasive strands 16 , and a mechanosensitive pathway, in which cellular confinement directly causes deformations of the cell nuclei accompanied by chromatin remodelling 69 . Here we showed evidence that EMT is also a mechanism involved in 3D unjamming transitions by regulating cell-matrix interplay.…”
Section: Discussionmentioning
confidence: 99%